Malaria in pregnant women between March 2002 and July 2003: experience in Hospital Regional de Loreto, Peru - Ramal Asayag, César (2018)
Introduction: Malaria is an endemic parasitic disease in northern Peru, both in the coast and in the jungle. There is still poor knowledge about the incidence of malaria in pregnant women, as well as about congenital malaria and some associated variables.Objective: To determine the cumulative incidence of malaria in pregnant women during a 15-month period in Hospital Regional de Loreto, and to determine the incidence of congenital malaria.Material and Method: An analytical epidemiological study aiming to determine the association between malaria in pregnant women and: low birth weight, prematurity, prior malaria infection, first pregnancy, being less than 21 years old, and the presence of fever with malaria, using statistical inference, odds ratios and confidence intervals, chi squares and p statistics.Results: The cumulative incidence of malaria in pregnant women followed for 15 months was 15,3%. No cases of congenital malaria were found. There is an association between malaria in pregnant women and low birth weight (p= 0,0001855), prematurity (P= 0,0214822), and a prior malaria infection (p= 0,0000281). There was no association between malaria and being a first pregnancy or being less than 21 years old. Other important findings were the association between P. falciparum malaria and fetal deaths during pregnancy (p= 0,0196497), and that average hematocrit and hemoglobin values are smaller in pregnant women with malaria compared to pregnant women without malaria.Conclusions: The study about malaria in pregnant woman found a significant association of this infection with low birth weight and prematurity. Malaria caused by P. falciparum during pregnancy is associated with fetal death there were no cases of congenital malaria.